Real-time Implementation of a xAVS Video Decoder - Qing Chang; Xin Liu; YaoLi Wang (Institute of Advanced Engineering and Science, 2014)
AVS video decoder consumes a huge number of computation, so real-time implementation of an AVS decoder has some challenging on x86 computing platform. This article describes a xAVS open source project to solve this problem. First of all, the reason for the low efficiency of the code of the existing AVS video decoder open source reference software RM52J_r1 is analyzed according to the description of AVS key technologies and decoding principles in the official documentation. Then according to the main problems of the reference software, re-design the optimized xAVS decoder architecture, and real-time property significantly improved with C code. Finally, use the x86 platform multimedia instruction sets to further optimize xAVS semantic processor. The experimental results show that, under the precondition of ensuring the quality of decoding, the decoding speed of the xAVS decoder for D1 has increased more than 14 times, to fully meet the needs of real-time decoding. DOI : http://dx.doi.org/10.11591/telkomnika.v12i6.5473